2014
DOI: 10.1186/1471-2407-14-321
|View full text |Cite
|
Sign up to set email alerts
|

Smoking increases rectal cancer risk to the same extent in women as in men: results from a Norwegian cohort study

Abstract: BackgroundSmoking has recently been established as a risk factor for rectal cancer. We examined whether the smoking-related increase in rectal cancer differed by gender.MethodsWe followed 602,242 participants (49% men), aged 19 to 67 years at enrollment from four Norwegian health surveys carried out between 1972 and 2003, by linkage to Norwegian national registries through December 2007. Hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated by fitting Cox proportional hazard models and adjustin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…Therefore, there may be a residual confounding effect of smoking on the risk of lung cancer. Smoking is also associated with cervical and rectal cancer, which may explain why we find inverse association between hyperemesis and risk of these cancers. Furthermore, smoking is reported to reduce the risk of thyroid cancer, but the results are conflicting .…”
Section: Discussionmentioning
confidence: 76%
“…Therefore, there may be a residual confounding effect of smoking on the risk of lung cancer. Smoking is also associated with cervical and rectal cancer, which may explain why we find inverse association between hyperemesis and risk of these cancers. Furthermore, smoking is reported to reduce the risk of thyroid cancer, but the results are conflicting .…”
Section: Discussionmentioning
confidence: 76%
“…We had previously examined the sex-specific associations between smoking and colon ( 17 ) and rectal ( 18 ) cancer in a large Norwegian cohort including 600,000 men and women. The results from these studies suggested that female smokers may be more susceptible to colon cancer ( 17 ) but not rectal cancer ( 18 ) in comparison with male smokers. Male former smokers had a higher risk of left colon cancer ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rectal cancer spreads more frequently to the thoracic organs, bone and nervous system and less frequently to peritoneum compared to colon cancer [5]. Age, gender, smoking and diabetes mellitus are risk factors of rectal cancer [68]. …”
Section: Introductionmentioning
confidence: 99%